Evaluasi Pengelolaan Kurikulum Berdasarkan Fungsi Dasar Manajemen Pendidikan Islam: Studi Kasus di MTS Persis 23 Cirengit - Sriwiguna, Riris; Mulyawan Shafwandy Nugraha (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Curriculum management is a strategic component of Islamic education because it plays an important role in achieving educational objectives and internalizing Islamic values within the learning process. Nevertheless, in practice, many schools continue to face managerial challenges in implementing the curriculum effectively. This study aims to evaluate curriculum management at MTs Persis 23 Cirengit based on the core functions of Islamic Educational Management, namely Planning, Organizing, Actuating, and Controlling (POAC). The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed using an interactive analysis model. The findings reveal that the POAC functions have been formally applied but have not yet operated as an integrated managerial cycle oriented toward continuous quality improvement. Curriculum planning remains largely procedural, organizing is not sufficiently participatory, implementation depends heavily on individual teacher capacity, and supervision is mostly administrative with limited follow-up actions.